Online video-based resistance training improves the physical capacity of junior basketball athletes - Klusemann, M.; Pyne, D. B.; Fay, T.; Drinkwater, E. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Junior basketball athletes require a well-designed resistance training program to improve their physical development. Lack of expert supervision and resistance training in junior development pathways may be overcome by implementing an online video-based program. The aim of this study was to compare the magnitude of improvement in physical performance, strength and functional movement patterns of junior basketball athletes employing either a fully supervised, or an online video-based resistance training program. Methods: Thirty-eight junior basketball athletes (males n=17; age 14±1y; height 1.8±0.1m; mass 67±12kg; females n=21; age 15±1y; height 1.7±0.1m; mass 62±8 kg;mean±SD) were assigned into a supervised resistance training group (SG, n=13), video training group (VG, n=13) or control group (CG, n=12) and participated in a six week controlled experimental trial. Pre- and post-testing included measures of physical performance (20 m sprint, step-in vertical jump, agility, sit and reach, line drill, Yo-Yo intermittent recovery level 1), strength (15 s push up and pull up) and functional movement screening (FMS). Results: Training logs revealed 96% compliance from the supervised group and 77% compliance from the video group. Both SG and VG achieved 3-5% ±2-4% (mean ±90% confidence limits) greater improvements in several physical performance measures (vertical jump height, 20 m sprint and Yo-Yo endurance performance) and a 28 ±21% greater improvement in push up strength compared to the CG. The SG attained substantially larger gains in FMS scores than both the VG (12 ±10%) and CG (13 ±8%). Discussion: Both short-term supervised and online video-based resistance training were effective in improving physical performance measures and strength. Supervised training remains the best method of program delivery to achieve maximum compliance, improvements in physical performance and functional movement patterns. In circumstances where supervised training is not available, online video-based training could be used to elicit substantial improvements in physical performance and strength in junior basketball athletes. This form of media-based training is a cost-effective and practical solution to apply resistance training to a large and/or remote athlete group. Sporting bodies could utilise this strategy to educate coaches and athletes on how to implement resistance training exercises into their daily training environment and enhance the short-term physical development of junior athletes.